Pengembangan Bahan Ajar Ilmu Pengetahuan Sosial Berbasis Budaya Dan Kearifan Lokal Masyarakat Pandalungan Di Kabupaten Jember Untuk Siswa Sekolah Menengah Pertama / Madrasah Tsanawiyah: The Development of Social Science Teaching Materials Based on the Culture and Local Wisdom of the Pandalungan Community in Jember Regency for Junior High School / Madrasah Tsanawiyah Students - Musyarofah Musyarofah; Anindya Fajarini (Fenomena, 2018)
Current social studies learning tends to be non-contextual as teachers have not optimally utilized local cultural potential. In fact, a local wisdom-based approach helps students understand social studies concepts and increases appreciation for their culture. This study aims to develop social studies teaching materials based on the culture and local wisdom of the Pandalungan Community in Jember Regency and determine their feasibility. The research employed a modified Borg & Gall model consisting of seven stages: preliminary research, planning, product development, initial trial, revision, main field trial, and final product. Validation results from material experts reached 80%, design experts 73.33%, linguists 83%, and social studies teachers 92.17%. The initial trial obtained an average of 85.66%, the main field trial applicability test reached 85.16%, and student learning outcomes achieved 100% completeness exceeding the minimum competency limits. The teaching materials are declared valid and feasible for use. Recommendations include disseminating the product to a wider scope and developing for other sub-themes with different learning approaches such as PBL. Pembelajaran IPS saat ini cenderung tidak kontekstual karena guru belum memanfaatkan potensi budaya lokal secara optimal. Padahal pendekatan berbasis kearifan lokal mampu membantu siswa memahami konsep IPS dan meningkatkan apresiasi terhadap budayanya. Penelitian ini bertujuan mengembangkan bahan ajar IPS berbasis budaya dan kearifan lokal Masyarakat Pandalungan di Kabupaten Jember serta mengetahui kelayakannya. Penelitian menggunakan model Borg & Gall yang dimodifikasi menjadi tujuh tahap: penelitian pendahuluan, perencanaan, pengembangan produk, uji coba awal, revisi, uji coba lapangan utama, dan produk akhir. Validasi oleh ahli materi mencapai 80%, ahli desain 73,33%, ahli bahasa 83%, dan guru IPS 92,17%. Uji coba awal memperoleh rata-rata 85,66%, uji keterterapan lapangan utama 85,16%, dan hasil belajar siswa tuntas 100% melampaui batas minimal kompetensi. Bahan ajar dinyatakan valid dan layak digunakan. Rekomendasi penelitian ini adalah perlunya diseminasi produk ke lingkup yang lebih luas serta pengembangan untuk subtema lain dengan pendekatan pembelajaran berbeda seperti PBL.